Ouerbegeleiding in die nuwe Suid-Afrika: voorvereiste vir beter matriek-uitslae? - Hay, Driekie (Koers, 1999)
Parent support programmes in the new South Africa: prerequisite for better matric results?The 1997 matriculation results with a fa ilu re rate of 52,9%, once again caused great concern country-wide (Jansen, 1998:56). With the exception of M pumalanga, the pass rate of all the provinces has decreased (Duffy, 1998:10). Five years after apartheid and with a new education dispensation being applied, the expected outcomes in terms of better matriculation results have not yet been realised (Haasbroek, 1998:12-13). The effect of this failure rate is extensive. During the 1993/1994 tax year matric failures cost South Africa R2,38 milliard. This is 13% of the total education budget (Die Volksblad, 1995:12-30). The extent of the 1997 failures has not yet been calculated in financial terms. In educational ranks there is as yet uncertainty regarding the possible manner in which this problem might be addressed. Is the solution to be found in more schools, in lower teacher-pupil ratios, or in other resources? A possible intervention strategy might probably be that of parent accompaniment. The home should indeed be the place where the young child should feel safe enough so that his/her potential might develop to the full. If the parent, for whatsoever reason, does not meet this responsibility, the total personal and intellectual development of the child is impeded.